IMPLEMENTASI PENDEKATAN LEAN MANUFACTURING DENGAN BERBAGAI METODE DI INDUSTRI FARMASI UNTUK MENINGKATKAN EFEKTIVITAS PROSES PRODUKSI - Nurul Asih Ramadhani; Sriwidodo, Sriwidodo (Journal of Innovation Research and Knowledge, 2024)
The development of the pharmaceutical industry in particular and the industrial world in general has forced the industry to apply production efficiency principles. The Lean Manufacturing approach is an operational strategy that is oriented towards achieving the shortest possible cycle time by eliminating waste, a production system capable of increasing value added. This review article aims to provide an overview of the application of Lean Manufacturing which can reduce waste so as to increase the effectiveness of the production process in the pharmaceutical industry. The preparation of this article review was carried out by searching the literature online. In the results of the review, there are several methods discussed regarding methods in the Lean Manufacturing approach, namely Six Sigma, Value Stream Mapping (VSM), Single Minute of Exchange Die (SMED), and Takt Time